Implementation Of English Language Learning And Islamic Character Development At Ibadurrahman Boarding School (IDBS) Duri: A Case Study At Ninth Grade - Andriani, Welly (Unit Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Agama Islam Hubbulwathan, Duri, Indonesia, 2024)
This study used a qualitative approach with a case study design to explore the implementation of the English education program at Ibadurrahman Boarding School (IDBS) Duri, Riau. The research participants included grade IX students categorized by high, medium, and low academic performance, as well as teachers and school staff. The research findings show that English language learning activities at IDBS Duri are highly structured and disciplined, starting from morning until afternoon. Students demonstrate high academic achievements in English subjects, supported by additional tutoring from competent teachers. Participation in English extracurricular activities is also very high, which helps students develop communication skills and confidence. Additionally, IDBS Duri has successfully integrated Islamic values into English learning through contextual approaches and religious activities. In conclusion, IDBS Duri has created a holistic English education environment, combining academic aspects and Islamic character development. This approach not only enhances students' academic achievements but also helps them develop into individuals with noble character and high ethics. This study can serve as a model for other schools in implementing a comprehensive English education program.